Self-assembled block polymer aggregates in selective solution: controllable morphology transitions and their applications in drug delivery. (2nd July 2020) - Jiao, Weiqi; Yang, Hu; Wu, Zimei; Liu, Jianping; Zhang, Wenli
ABSTRACT: Introduction: Amphiphilic block copolymers are able to self-assemble into rich morphologies with high controllability for drug delivery. Great efforts have been made for decades to construct efficient drug delivery systems (DDSs) using nanostructured self-assemblies to overcome the drawbacks of pharmaceuticals, such as low aqueous solubility, premature drug release during circulation, and undesirable side effects. Areas covered: Here we review the researches of self-assembled block polymer aggregates with a focus on the shape-forming and shape-changing mechanisms, and applications of controlling morphology transition by multiple factors in drug delivery. We tend to provide a comprehensive description of the connection between structure-changing thermodynamics, kinetics, and influencing factors, thus to enlighten more pathways for future developments in the field of drug delivery. Expert opinion: By understanding the underlying mechanisms for the structure formation and transition, it enables versatile applications in DDSs design by altering drug morphologies. However, developing more sophisticated and multifunctional polymeric nanocarriers is still challengeable in the clinical application, which would hold considerable potential in promoting the efficiency in morphology control to achieve higher intelligence of drug delivery.